The effect of using tangram-based puzzle media on students’ learning interest and creative thinking skills - Rachmania Diandini; Bagus Ardi Saputro; Henry Januar Saputra (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This present study aims to determine the effect of tangram-based puzzle media on improving fourth-grade students' learning interest and creative thinking skills. It is motivated by the issue of low interest in learning mathematics and the limited availability of concrete learning media, which often leads to conventional teaching methods. This study employs a One-Group pretest-posttest design. Data were collected through interviews, written tests, questionnaires, and documentation. The study results indicate that tangram-based puzzle media successfully fostered and maintained students' learning interest, as evidenced by increased student attention, interest in learning, feelings of pleasure, and increased student involvement. A significant increase was also observed in creative thinking skills, including enhancements in fluency, flexibility, originality, and elaboration skills. The research results indicate that increased interest in learning facilitates the practical understanding of quadrilateral concepts and develops creative thinking skills. Thus, Tangram-based puzzle media are a valuable and innovative learning tool to enable more interactive mathematics learning and develop higher-order thinking skills.